Traditional Chinese medicine derived exosome-like nanovesicles in wound repair and skin regeneration - Wang, Kang; Yang, Zi-Ting; Wang, Fei; Ma, Yun-Qi; Qing, Yong; Zhang, Zhen-Yu (Frontiers in Cell and Developmental Biology, 2025)
Skin injuries, including acute wounds, burns, and chronic ulcers, pose significant clinical challenges due to their potential to cause delayed healing and functional impairment. Exosome-like nanovesicles (ELNVs) derived from traditional Chinese medicinal (TCM) herbs have recently emerged as promising natural agents for skin repair and regeneration. These nanoscale vesicles combine the structural advantages of plant-derived delivery systems with the inherent pharmacological activities of TCM phytochemicals, offering dual roles as both bioactive agents and therapeutic carriers. Accumulating evidence indicates that TCM-derived ELNVs modulate key processes in wound healing, including inflammation resolution, fibroblast and keratinocyte activation, angiogenesis, and oxidative stress reduction. Moreover, certain vesicles have demonstrated potential in promoting hair follicle regeneration and protecting against photoaging, further highlighting their relevance in functional skin restoration. Compared with vesicles from common edible plants, TCM-ELNVs benefit from standardized cultivation, well-established traceable sourcing systems, and consistent phytochemical profiles, enhancing their suitability for therapeutic development. This review summarizes recent progress in the characterization, biological functions, and preclinical applications of TCM-derived ELNVs in cutaneous healing. Special attention is given to their mechanisms of action and their potential to serve as platforms for drug delivery and regenerative therapies. Overall, TCM-ELNVs represent a promising class of bioactive nanovesicles with broad translational potential in wound repair and skin regenerative medicine.